Behavioural modelling using the MOESP algorithm, dynamic neural networks and the Bartels–Stewart algorithm - Schilders, W.H.A.; Meijer, P.B.L.; Ciggaar, E. (Applied numerical mathematics, 2008)
In this paper we discuss the use of the state-space modelling MOESP algorithm to generate precise information about the number of neurons and hidden layers in dynamic neural networks developed for the behavioural modelling of electronic circuits. The Bartels–Stewart algorithm is used to transform the information from the MOESP algorithm to the neural network formalism. The technique is related to the class of model order reduction algorithms that receives much attention in recent years, especially in the electronics industry.